Relationship between eating attitude and attention deficit and hyperactivity disorder in a group of bariatric surgery candidates: A pilot study (Annals of Medical Research, 2021)
Aim: Attention deficit and hyperactivity disorder (ADHD) is more common in bariatric surgery candidates who are more failed to lose weight. We decided to evaluate eating attitudes and ADHD in a group of bariatric surgery candidates.Material and Methods: We created a study group from bariatric surgery candidates (n=40) from outpatient psychiatry clinic of Haydarpasa Numune Training and Research Hospital. Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), Wender-Utah Rating Scale (WURS), Adult attention deficit disorder/attention deficit hyperactivity disorder (ADD/ADHD), DSM IV- based diagnostic screening and rating scale, Beck depression inventory (BDI) and eating attitude test (EAT) were applied to all participants.Results: 77.5% of 40 bariatric surgery candidates (n=31) were women. Rate of childhood ADHD was 17.5% based to WURS cut off point. Rate of adult ADHD was found 7.5%. Mean point of total Adult ADD/ADHD DSM IV- based diagnostic screening and rating scale score was 36.12±20.55. Mean point of attention deficit score was 6.35±4.62, hyperactivity score was 6.07±4.99 and related properties score was 23.72±13.86. Mean point of EAT was 24.20±10.61. Mean point of BDI score was 14.05±+9.47.Conclusion: Symptoms of adult ADHD, childhood ADHD, disordered eating patterns and high levels of depressive symptoms are common and that they are positively correlated in bariatric surgery candidates (BSCs). Some factors about ADHD (total ADHD score and related factors with ADHD) have a clear association with eating attitude. All these factors must be taken into consideration by treatment team of BSCs.